2016
DOI: 10.18203/2320-1770.ijrcog20161590
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of antepartum and postpartum eclampsia at a tertiary care centre

Abstract: Background: Hypertensive disorders complicate 5 to 10 percent of all pregnancies. Eclampsia is one of the dreaded complications of preeclampsia and remains one of the leading causes of maternal deaths in our country. The incidence of post-partum eclampsia is on the rise. Our aim was to study the incidence, demographical factors, and clinical profile associated complications, perinatal and maternal outcomes in pregnancies complicated with antepartum and postpartum eclampsia and compare between the two groups. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The incidence of eclampsia in this study reported was 68.8% (124/180) in women below the age of 25 years which is comparable with the studies conducted by Bembalgi et al (59.2%). 8 Present study showed 74.4% (134/180) of cases were primigravida while 25.6% (36/180) of cases were multi gravida which is comparable to studies by Sunita et al in which it is 79 and 21% respectively. 9 It suggests primigravida patients are predisposed to the risk of preeclampsia as they are exposed to chorionic villi for the first time.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of eclampsia in this study reported was 68.8% (124/180) in women below the age of 25 years which is comparable with the studies conducted by Bembalgi et al (59.2%). 8 Present study showed 74.4% (134/180) of cases were primigravida while 25.6% (36/180) of cases were multi gravida which is comparable to studies by Sunita et al in which it is 79 and 21% respectively. 9 It suggests primigravida patients are predisposed to the risk of preeclampsia as they are exposed to chorionic villi for the first time.…”
Section: Discussionsupporting
confidence: 89%